On the problem of interpreting Krotkaya’s suicide in F. M. Dostoevsky’s novel Krotkaya/A gentle creature - Lukashova, Alina (Vilnius University Open Series, 2024)
The article examines Fyodor Dostoevsky’s story Krotkaya (also titled A Gentle Creature) in the context of the interpretation of the main character’s suicide and provides a brief overview of opposing interpretations of the work. Despite the abundance of different interpretations, from biographical to religious connotations of the story, little attention has been paid to interpretations using a psychological approach. In connection with these, the author of the article proposes to expand the interpretation of the main character’s suicide from moral and ethical to psychological motives, by relying on the theory of destructive attraction developed by Sabina Spielrein. The article characterizes the concept of destructive drive and pays special attention to the issue of illustrations of the manifestation of the destructive drive directly from the main character of the story.
Keywords: Dostoevsky; Spielrein; A Gentle Creature; suicide; destruction